Inhibition of the oxidative stress-induced miR-125b protects glucose metabolic disorders of human retinal pigment epithelium (RPE) cells - Liu, Gang; Zhang, Chun-Di; Wang, Jing; Jia, Wan-Cheng (Cellular and Molecular Biology, 2018)
The dysfunction of retinal pigment epithelium (RPE) with aging leads to age-related macular degeneration (AMD). Oxidative stress has been demonstrated as one of the causes of retinal pathological conditions. This study was conducted to investigate the mechanism of hydrogen peroxide (H2O2) induced human retinal pigment epithelial (RPE) cell dysfunction. We report miR-125b is induced by H2O2 treatments in RPE cells. In addition, we observed inhibited glucose metabolism under oxidative stress. Overexpression of miR-125b promotes the disorders of cellular glucose metabolism through direct targeting Hexokinase 2 (HK2). Restoration of HK2 in H2O2 treated RPE cells prevents the oxidative stress-suppressed glucose metabolism. Inhibition of the H2O2-induced miR-125b by inhibitor significantly prevented disorders of glucose metabolism. This study will contribute to the development of the miRNA based therapeutic approaches for against the oxidative stress-mediated human AMD.